Differential Effects of D-Galactose Supplementation on Golgi Glycosylation Defects in TMEM165 Deficiency - Durin, Zoé; Houdou, Marine; Morelle, Willy; Barré, Lydia; Layotte, Aurore; Legrand, Dominique; Ouzzine, Mohamed; Foulquier, François (Frontiers in Cell and Developmental Biology, 2022)
Glycosylation is a ubiquitous and universal cellular process in all domains of life. In eukaryotes, many glycosylation pathways occur simultaneously onto proteins and lipids for generating a complex diversity of glycan structures. In humans, severe genetic diseases called Congenital Disorders of Glycosylation (CDG), resulting from glycosylation defects, demonstrate the functional relevance of these processes. No real cure exists so far, but oral administration of specific monosaccharides to bypass the metabolic defects has been used in few CDG, then constituting the simplest and safest treatments. Oral D-Galactose (Gal) therapy was seen as a promising tailored treatment for specific CDG and peculiarly for TMEM165-CDG patients. TMEM165 deficiency not only affects the N-glycosylation process but all the other Golgi-related glycosylation types, then contributing to the singularity of this defect. Our previous results established a link between TMEM165 deficiency and altered Golgi manganese (Mn2+) homeostasis. Besides the fascinating power of MnCl2 supplementation to rescue N-glycosylation in TMEM165-deficient cells, D-Gal supplementation has also been shown to be promising in suppressing the observed N-glycosylation defects. Its effect on the other Golgi glycosylation types, most especially O-glycosylation and glycosaminoglycan (GAG) synthesis, was however unknown. In the present study, we demonstrate the differential impact of D-Gal or MnCl2 supplementations on the Golgi glycosylation defects caused by TMEM165 deficiency. Whereas MnCl2 supplementation unambiguously fully rescues the N- and O-linked as well as GAG glycosylations in TMEM165-deficient cells, D-Gal supplementation only rescues the N-linked glycosylation, without any effects on the other Golgi-related glycosylation types. According to these results, we would recommend the combined use of D-Gal and MnCl2 for TMEM165-CDG therapy.